Implication of alterations in Parkin gene among North Indian patients with colorectal cancer - Raj Ranjan Tiwari; Raj Ranjan Tiwari; Khushnuma Wahabi; Ahmad Perwez; Zafar Iqbal Bhat; Syed Shamimul Hasan; Sundeep Singh Saluja; Moshahid Alam Rizvi (Turkish Journal of Gastroenterology, 2020)
Background/Aims: Alterations in Parkin (PRKN) have been described in many cancers; however, the molecular mechanism that contributes to loss of Parkin expression in colorectal cancer (CRC) remains unclear. The aim of this study was to investigate the involvement of PRKN mutation and loss of heterozygosity (LOH) in loss of Parkin expression. To understand the role of PRKN in cancer progression, we also evaluated the association of Parkin expression with clinicopathological parameters in North Indian population. Materials and Methods: We studied 219 CRC samples and their adjacent normal tissues (control) obtained from North Indian patients with CRC. The expression of Parkin was analyzed by immunohistochemistry (IHC). PRKN mutations were analyzed by single-stranded conformational polymorphism (SSCP) and sequencing. For loss of heterozygosity (LOH), we employed two intragenic, D6S305 and D6S1599, and one telomeric marker, D6S1008. Results: In our study, we found four novel somatic mutations, namely, C166G, K413N, R420P (exon 4), and V425E (exon 11). Both mutation in Parkin (p = 0.0014) and LOH (p = 0.0140) were significantly associated with loss of Parkin expression. Additionally, Parkin mutations were not associated with the clinicopathological parameters of the patients. Furthermore, both, LOH in Parkin and Parkin expression were significantly correlated with different clinicopathological variables (p<0.05). Conclusion: Our results indicate that Parkin expression is not regulated by a single mechanism, but both mutation and LOH contribute to loss of Parkin expression. We also provide evidence of involvement of Parkin in metastasis and cancer progression. We, therefore, suggest Parkin as a potential prognostic marker and warrant further analysis in this direction. Cite this article as: Tiwari RR, Wahabi K, Perwez A, et al. Implication of alterations in Parkin gene among North Indian patients with colorectal cancer. Turk J Gastroenterol 2020; 31(3): 211-20.